2017
DOI: 10.1002/ijc.30544
|View full text |Cite
|
Sign up to set email alerts
|

Examining temporal effects on cancer risk in the international nuclear workers’ study

Abstract: The paper continues the series of publications from the International Nuclear Workers Study cohort (INWORKS) that comprises 308,297 workers from France, the United Kingdom and the United States, providing 8.2 million person-years of observation from a combined follow-up period (at earliest 1944 to at latest 2005). These workers' external radiation exposures were primarily to photons, resulting in an estimated average career absorbed dose to the colon of 17.4 milligray. The association between cumulative ionizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
2
16
0
5
Order By: Relevance
“…Given this pattern, one might expect to observe an increased excess risk with the use of shorter lag periods in the analysis; however, this was not the case in the NRRW cohort in which risks were only found to decrease when lags of more than 20 years were used. This result is more consistent with a recently published study looking at temporal effects in the INWORKS cohort (25), in which excess leukemia risks were not observed in the first years after exposure, and the optimal lag period was 19 years. The temporal variation in risk within the NRRW cohort falls somewhere between these two options, with excess risks consistent across lag periods up to 20 years and with lower point estimates of ERR associated with doses received more than 25 years ago.…”
Section: Discussionsupporting
confidence: 91%
“…Given this pattern, one might expect to observe an increased excess risk with the use of shorter lag periods in the analysis; however, this was not the case in the NRRW cohort in which risks were only found to decrease when lags of more than 20 years were used. This result is more consistent with a recently published study looking at temporal effects in the INWORKS cohort (25), in which excess leukemia risks were not observed in the first years after exposure, and the optimal lag period was 19 years. The temporal variation in risk within the NRRW cohort falls somewhere between these two options, with excess risks consistent across lag periods up to 20 years and with lower point estimates of ERR associated with doses received more than 25 years ago.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we report on our analysis of non-cancer mortality with an emphasis on circulatory disease mortality. Analyses of deaths due to malignant disease have been reported previously (2224). …”
Section: Introductionmentioning
confidence: 99%
“…Our best fit models for certain cancers had lags longer than the 10‐20 years usually used in other studies. Daniels et al reported that temporal risk patterns appeared to vary by cancer type, and the excess risk of certain cancers may span several decades. Our report of late onset of exposure‐related mortality also suggested additional follow‐up of these workers to fully describe their lifetime risks.…”
Section: Discussionmentioning
confidence: 99%
“…The Akaike Information Criterion (AIC) was used to evaluate model fit. In addition, for each outcome, a grid search was used to find the lag that maximized the likelihood function . The hazard ratio (HR) at 50th and 75th percentiles of dose compared with the non‐exposed and corresponding 95% profile likelihood‐based confidence intervals (CIs) were derived with restriction to workers with no more than the 95th percentile of dose.…”
Section: Methodsmentioning
confidence: 99%